PERAN MASYARAKAT ADAT DALAM MENERAPKAN NILAI-NILAI LAUDATO SI' DI KABUPATEN SANGGAU - Tinenti, Hemma Gregorius; Bungan, Jimiana; Martinus, Martinus; Nirwana, Theresia Nobel Cory (CREDENDUM: Jurnal Pendidikan Agama, 2025)
This study aims to explore how Indigenous Catholic communities in Sanggau Regency embody and apply the values of Laudato Si’ in their daily lives, even without formal theological exposure to the document. Using a qualitative approach and case study method, this research examines the ecological practices, cultural beliefs, and community-based efforts of Indigenous people in conserving their natural environment. The findings reveal that traditional values-such as viewing forests as sacred, practicing rotational agriculture, and maintaining balance with nature demonstrate a lived expression of integral ecology. However, their efforts face significant challenges, including deforestation, land grabbing, economic marginalization, and lack of institutional support. This study underscores the importance of recognizing Indigenous communities not only as victims of ecological degradation but also as active agents of environmental stewardship. It recommends a stronger partnership between the Catholic Church and Indigenous communities through contextual ecological pastoral approaches that affirm cultural identity, ecological justice, and intergenerational sustainability.